ATRA treatment slowed P-selectin-mediated rolling of flowing HL60 cells in a mechano-chemical-dependent manner - Dong, Xiaoting; Peng, Shiping; Ling, Yingchen; Huang, Bing; Tu, Wenjian; Sun, Xiaoxi; Li, Quhuan; Fang, Ying; Wu, Jianhua (Frontiers in Immunology, 2023)
All-trans retinoic acid (ATRA)-induced differentiation of acute promyelocytic leukemia (APL) toward granulocytes may trigger APL differentiation syndrome (DS), but there is less knowledge about the mechano-chemical regulation mechanism of APL DS under the mechano-microenvironment. We found that ATRA-induced changes in proliferation, morphology, and adhesive molecule expression levels were either dose- or stimuli time-dependent. And an optimal ATRA stimulus condition for differentiating HL60 cells toward neutrophils consisted of 1×10-6 M dose and 120 h stimulus times. Under wall shear stresses, catch-slip bond transition governs P-selectin-mediated rolling for neutrophils and untreated or ATRA (1×10-6 M, 120h)-treated HL60 cells. ATRA stimuli slowed the rolling of HL60 cells on immobilized P-selectin down no matter whether ICAM-1 was engaged. The β2 integrin near the PSGL-1/P-selectin axis would be activated within sub-seconds for each cell group mentioned above, contributing to slow rolling. A faster β2 integrin activation rate and the higher expression levels of PSGL-1 and LFA-1 were assigned to induce the over-enhancement of ATRA-treated HL60 adhesion in flow, causing APL DS development. These findings provided an insight into the mechanical-chemical regulation mechanical for APL DS development via ATRA-treatment of leukemia and a novel therapeutic strategy for APL DS by targeting the relevant adhesion molecules.